MongoDB high availability - Mehrabani, Afshin (Community experience distilled., 2014)
In Detail MongoDB is one of the pioneers in implementing the NoSQL concept by using "Document" as the infrastructure to save and restore data from a database. Using MongoDB in high pressure situations needs a predefined plan, and this book with its step-by-step approach can help you to make a highly available MongoDB server using the latest features. Starting with the basic concepts and their implementation, you will study real-world use cases which will help you understand the practical aspects of MongoDB. Each step contains an in-depth presentation and several screenshots. This book teaches you all the tips and tricks to make a highly available MongoDB server using different clustering solutions. This book has a perfect balance of concepts and their practical implementation along with solutions to make a highly available MongoDB server in a production environment and under high throughput with clear instructions and guidance. Approach This book has a perfect balance of concepts and their practical implementation along with solutions to make a highly available MongoDB server with clear instructions and guidance. Who this book is for If you are using MongoDB in a production environment and need a solution to make a highly available MongoDB server, this book is ideal for you. Familiarity with MongoDB is expected so that you understand the content of this book.